2019
DOI: 10.1002/ejlt.201900317
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Productivity for Aqueous Biphasic Hydroformylation of Methyl 10‐Undecenoate: A Detailed Phase Investigation

Abstract: The overall productivity of the aqueous biphasic hydroformylation of the castor oil-derived methyl 10-undecenoate is increased. To increase the reaction rate, the miscibility of water and the fatty compound is increased by addition of the green solvent 1-butanol as co-solvent. For the first time, the concentration of solvents, substrate, and product within the reaction process is experimentally examined in a biphasic system under 20 bar pressure of synthesis gas and 140°C. A reactor to get samples of both phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…First, as we have already shown in the section Recycling Limitations, water formation has a slightly negative influence on the reaction performance and selectivity. The water accumulation could cause the homogeneous mixture to decompose into a biphasic system, suffering from liquid–liquid phase limitations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, as we have already shown in the section Recycling Limitations, water formation has a slightly negative influence on the reaction performance and selectivity. The water accumulation could cause the homogeneous mixture to decompose into a biphasic system, suffering from liquid–liquid phase limitations …”
Section: Resultsmentioning
confidence: 99%
“…The water accumulation could cause the homogeneous mixture to decompose into a biphasic system, suffering from liquid−liquid phase limitations. 47 Catalyst leaching, water formation, and accumulation in the polar catalyst phase could be a reason for the decreasing activity from run 4 onward. A third factor decreasing the reaction rate might be catalyst deactivation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In previous investigations, it was revealed that sulfonated ligands have a high affinity to dimcarb and can be used to effectively retain homogeneous catalysts in the polar dimcarb phase during the separation of the amine products. , Xantphos (Figure , right), having a comparable natural bite angle ( β n = 111°,) to DPEphos (Figure , left; β n = 102°,), has been used in the ruthenium-catalyzed alcohol amination to study the mechanism by our group and is, therefore, a well-established ligand for this reaction . Surprisingly, Sulfoxantphos (Figure , right; R = SO 3 Na), the sulfonated analogue of Xantphos, was never used for alcohol amination, although it was successfully applied in several other homogeneously catalyzed biphasic reactions. Moreover, Sulfoxantphos shows similar selectivities in the rhodium-catalyzed hydroformylation as the nonsulfonated Xantphos, which indicates that it coordinates in the same way . After consideration of the absolute solubility of Xantphos (1.8 × 10 –3 mmol g –1 ) and Sulfoxantphos (324.6 × 10 –3 mmol g –1 ) in dimcarb at 25 °C, we decided to use Sulfoxantphos for further investigations.…”
Section: Resultsmentioning
confidence: 99%
“…However, after the first run, the conversion decreases to around 50 % and remained almost constant for nine additional runs. The same authors [106] extended this study for the valorization of methyl 10-undecenoate using a jet-loop reactor (JLR) for this biphasic system, in which intensive mixing was achieved to overcome the solubility limitations. [107] The low solubility of long-chain olefins in water often result in low olefin conversion in the biphasic hydroformylation reactions.…”
Section: Homogeneous and Biphasic Systemsmentioning
confidence: 99%